Community forest concessionaires: resisting green grabs and producing political subjects in Guatemala. Issue 3 (19th March 2018) - Devine, Jennifer A.
Abstract : In 2005, Guatemalan community forest concessionaires achieved a remarkable legislative victory that reversed a green land grab in the Maya Biosphere. The fight over this space, the Mirador Basin, provides valuable contributions to analyses of global land grabs, grassroots politics and power relations underpinning environmental governance. First, the fight for the Mirador Basin illustrates how green land grabs create new natures, rather than simply enclosing existing green spaces. Second, it contributes to recent scholarship detailing land-grabbing practices of resistance, acquiescence and incorporation 'from below' by describing how Maya Biosphere community forest concessionaires were able to reverse a green grab. Lastly, I argue this successful reversal largely rests on the articulation and mobilization of a new rights-bearing subject – the forest concessionaire. Struggles for land in the Maya Biosphere illustrate that practices and relations of green governance do not always create disciplined, neo-liberal, green subjects. Rather, community forestry has provided a political platform turning reserve residents into influential actors participating in the re-territorialization of power in contemporary Guatemala.